2018
DOI: 10.12693/aphyspola.133.1215
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Magnetic Properties of Pt/Co/Pt Films by Ga+ Ion Irradiation: Focused versus Uniform Irradiation

Abstract: 30 keV Ga + irradiation-induced changes of magnetic and magneto-optical properties of sputtered Pt/Co/Pt ultrathin trilayers films have been studied as a function of the ion fluence. Out-of-plane magnetic anisotropy states with enhanced magneto-optical effects were evidenced for specific values of cobalt thickness and irradiation fluence. Results obtained after uniform or quasi-uniform focused ion beam irradiation on either out-of-plane or in-plane magnetized sputtered pristine trilayers are compared. Similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
(131 reference statements)
0
1
0
2
Order By: Relevance
“…This possibility is corroborated by [28] where it is demonstrated that over a fluence of 10 14 ions/cm 2 the 2 blocks become ferromagnetically coupled and behave as a single thicker ferromagnetic layer. Accordingly, the loss of perpendicular Magnetic Anisotropy was documented in CoPt multilayers over 10 15 Ga + ions/cm 2 irradiation in [30] and in [31]. In particular, the substitution of Ta, as the cap layer, with W seems to be beneficial to avoid deleterious material inter diffusion [32].…”
Section: A H C Degradation and The Role Of Synthetic Antiferromagnetic Layermentioning
confidence: 97%
“…This possibility is corroborated by [28] where it is demonstrated that over a fluence of 10 14 ions/cm 2 the 2 blocks become ferromagnetically coupled and behave as a single thicker ferromagnetic layer. Accordingly, the loss of perpendicular Magnetic Anisotropy was documented in CoPt multilayers over 10 15 Ga + ions/cm 2 irradiation in [30] and in [31]. In particular, the substitution of Ta, as the cap layer, with W seems to be beneficial to avoid deleterious material inter diffusion [32].…”
Section: A H C Degradation and The Role Of Synthetic Antiferromagnetic Layermentioning
confidence: 97%
“…(a-f)不同剂量的 30 keV Ga + 辐照 Pt/Co/Pt 结构后测得的磁滞回线,以及剩磁与辐照剂量 之间的依赖关系 [36] ; Figure 1. (a-f)The measured hysteresis loops of 30 keV Ga + irradiated Pt/Co/Pt structures at different doses, and the dependence between remanence and irradiation dose [36] ; 除了能够降低垂直磁各向异性外,选用部分种类和能量的离子,可以使多层 膜结构转变为合金结构,并形成特殊的晶相,进而增大其垂直磁各向异性。T.…”
unclassified
“…Devolder [34] 等人利用 30 keV He + 在 0-3×10 16 促进的 Pt/Co 合金化主要发生在上界面,而下界面则发生由层间扩散引起的粗糙 度增加。J.Jaworowicz [35] 等人系统地研究了辐照导致样品合金化的规律以及内在 机制。他们的实验结果表明,在 30 keV Ga + 辐照 Pt/Co 结构的过程中,垂直各向 异性将随着剂量呈非单调的变化。这是由于界面混杂程度、形状各向异性、以及 形成的 L1 0 相 CoPt 晶体中的磁晶各向异性相互竞争所导致的。I.Sveklo [36] 等人 也得到了类似的结果。该实验结果显示,Co/Pt 多层膜在经过能量为 30 keV、 剂 量为 0-0.2×10 15 ,45 keV Xe + ,35 keV Kr + ,21 keV Ar + 在 0-4×10 16 ions/cm 2 剂量范围 内辐照了 PtCo [38] ,FePt [37] [39] ,FeRh [40] ,FePd [41] ,FeAl [42] ,NiMn [43] 结构,离 子与材料原子之间的弹性碰撞改变了原子排列,形成了新的晶相,有效的改变了 其化学有序度,弱磁各向异性转变为强磁各向异性。但在 O.Hellwig 等人的实验 中,700 keV N + 辐照 Pt/Cr/Co 结构后,Cr 和 Pt 的原子位置会随机化,这导致了 化学无序和非磁性相的形成 [44] 。 在应用方面, T.Devolder 等利用 15 keV He + 在 0-4×10 19 ions/cm 2 的剂量 范围内辐照了 Ta/CoFeB/MgO 结构 [45] [46] 等人利用 400 keV Ar + 辐照了 MgO/FeCoB/W/FeCoB/MgO 多层膜结构,发现在辐照剂量为 6 1×10 13 -1×10 14 ions/cm 2 时,可以诱导出不同锥角的易锥态,如图 2a-2b 所示。 研究人员通过 80 keV Ar + ,200 keV Ar + 诱导了 CoPt [47] ,FeNi [48] 薄膜的单轴磁各 向异性, 并采用 X 射线衍射 (X-ray diffraction)和 X 射线发射光谱 (X-ray emission spectroscopy)验证了 CoPt 相的形成和非等效电子杂交是诱导 CoPt 单轴磁各向 异性的重要原因,图 2c-2f 展示了外加磁场方向与辐照方向共同调控 CoPt 各向 异性的过程。此外,P.Z.Li 等人证明了离子辐照能显著降低激光翻转垂直磁矩的 势垒,AOS(All-optical switching)阈值可以降低近 30% [49] 。在设置磁性图案化 方面,C.T.Rettner 等通过把 30 keV Ga + 、 He + 辐照与诱导磁场相结合,实 现了在 CoCrPt [50] ,Pt/Co/Pt [51] ,CoFeSiB [52] 材料中不同区域上的磁化强 [47] ; Figure 2. Ion irradiation-assisted preparation of structures with uniaxial anisotropy or easy cone anisotropy.…”
unclassified